Analisis Perilaku Hidup Bersih dan Sehat Pada Keluarga Yang Menjaga Pasien di Bidan Praktek Swasta Kota Langsa - Elvina sari (Inovasi Kesehatan Global, 2024)
PHBS is all health behavior carried out out of personal awareness so that the family and all its members are able to help themselves in the health sector and have an active role in community activities.This type of research uses qualitative research where this research uses questionnaires and interviews. This research design uses a phenomenology approach design, namely this approach seeks to reveal, study and understand the unique and unique phenomena and contexts experienced by individuals up to the level of belief of the individual concerned.Based on the research method carried out by the researcher, the researcher obtained the results that there were still some patient families who did not know what clean and healthy living behavior (PHBS) was in the hospital and did not believe that in treating patients health workers always behaved in a clean and healthy lifestyle., Meanwhile, some patients already know about clean and healthy living behavior (PHBS) in hospitals and believe that when treating patients, health workers always behave in a clean and healthy way.